Guarantying of passengers' security in international flights - Горян, Елла Володимирівна; Горян, Крістіна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
Legal mechanisms of passengers' security guarantying during international flights has been analyzed. Authors conclude that passengers' security is a result of effective international and national mechanisms. It'sbeen emphasized that successful experience of EU must be taken into consideration.